Association of Job Satisfaction, Intention to Stay, Organizational Commitment, and General Self-Efficacy Among Clinical Nurses in Riyadh, Saudi Arabia - Naif M. Alshaibani; Ahmad E. Aboshaiqah; Naif H. Alanazi (Behavioral Sciences)
Nurse turnover presents a significant challenge for healthcare organizations worldwide, impacting patient care quality and organizational stability. Understanding the determinants of nurse turnover, particularly job satisfaction, intention to stay, organizational commitment, and general self-efficacy, is crucial for developing effective retention strategies. This study aimed to explore the relationships among job satisfaction, intention to stay, organizational commitment, general self-efficacy, and demographic variables. A cross-sectional, correlational research design was employed, with data collected through validated questionnaires distributed to a total convenience sample of 227 clinical nurses in Riyadh, Saudi Arabia between July 2023 and August 2023. Validated measurement tools, including the Job Satisfaction Index, the Intent to Stay Scale, the Organizational Commitment Scale, and the General Self-Efficacy Scale, were utilized. Descriptive statistics were employed to summarize demographic information, and a correlation analysis was conducted to explore the relationships between the study variables. The findings revealed moderate levels of job satisfaction, intention to stay, organizational commitment, and general self-efficacy among the clinical nurses, with significant positive correlations observed among these variables as well as the nurses’ sociodemographic characteristics. Notably, clinical nurses constituted a significant portion of the sample, suggesting the need for targeted interventions tailored to this demographic group as well as non-Saudi nurses (expatriate nurses), particularly in enhancing their organizational commitment and self-efficacy. The study found significant and positive associations between the four study variables and the nurses’ demographic characteristics. Tailored interventions addressing job satisfaction, intent to stay, organizational commitment, self-efficacy, and demographic variables are essential for mitigating nurse turnover. By fostering a supportive work environment and implementing targeted retention strategies informed by demographic insights and determinants of turnover, healthcare organizations can enhance nurse retention rates and ensure a stable and fulfilled nursing workforce.